Evaluasi Cahaya pada Ruang Rawat Inap Pasien: Studi Kasus Rumah Sakit Universitas Sumatera Utara - Titi Santi Evriyanta Naibaho; Dwira Nirfalini Aulia; Achmad Delianur Nasution (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The light that enters a patient's inpatient wards is very influential in the comfort of the patient throughout his treatment and also influences the smoothness of the paramedics to carry out their activities. Therefore, this study was conducted by collecting data and lighting measurements on existing conditions and simulating the spread of light in the patient's inpatient wards by applying Ecotect software so that it can be seen whether the lighting meets the requirements or not, in accordance with the Indonesian National Standard (SNI) 03-6197-2000 as a standard procedure for average brightness recommended for inpatient wards. Then analyzing the lighting needs that are recommended materials from lighting elements so that they can be utilized in the patient's inpatient wards and meet SNI requirements.